2023
DOI: 10.1186/s12906-023-04007-7
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of sham acupuncture in randomised controlled trials: a critical review of the literature

Abstract: Background Sham acupuncture is usually used to assess the specific effects of acupuncture. However, the reporting quality of sham acupuncture remains unclear despite its critical importance in understanding and analyzing the effects of acupuncture. This paper presents a literature review aimed at assessing the quality of reporting of sham acupuncture in randomized controlled trials (RCTs) based on STRICTA 2010 and TIDieR-Placebo. Methods Three elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Interestingly, the non-acupoint shallow puncture produced even less placebo response than non-penetration acupuncture. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the non-acupoint shallow puncture produced even less placebo response than non-penetration acupuncture. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the non-acupoint shallow puncture produced even less placebo response than nonpenetration acupuncture. 33 This trial aims to address two key technical issues, namely the application of the SA treatment and patients' compliance. To ensure the appropriate administration of SA, all acupuncturists will receive extensive training before the commencement of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…The accidental inclusion of active components in a placebo treatment capable of triggering specific effects has been identified as a significant problem in placebo-controlled trials and is more common than had been previously thought [13][14][15]. The inadequate description of sham acupuncture techniques [16] and the lack of pre-clinical studies demonstrating the lack of specific effects with sham needling techniques [5] continue to plague this field, creating difficulties in interpreting the results from both clinical trials and systematic reviews when sham acupuncture is used as a control treatment [5].…”
Section: Methods Mattermentioning
confidence: 99%
“…head, neck and extremity acupoints). 15,19 Recent meta-analyses have shown that collectively the different styles of acupuncture are superior to sham needling 20 controls (e.g., placing acupuncture needles in non-acupoints, non-penetrating needles, or shallow needles) in the ED and other settings. 21,22 These studies have also demonstrated physiologic effects with needles beyond placebo, prompting experts to recommend the use of non-sham controls in larger pragmatic trials to assess treatment effectiveness of acupuncture.…”
Section: Introductionmentioning
confidence: 99%